School admissions: practical tips to prepare your child - Banerjee, Suschismita (India, 2006)
The books help you prepare your child for this new phase in their life. It attempts to break down the process of preparation into specific definable steps.
Keywords: Parent and Child; Parent Participation (Education); School Admissions (Nursery)